2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.259384
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Side Impact Injuries: Evaluation of Seat Belt Restraint System, Occupant Kinematics and Injury Potential

Abstract: Side impact crashes are the second most severe motor vehicle accidents resulting in serious and fatal injuries. One of the occupant restraint systems in the vehicle is the three point lap/shoulder harness. However, the lap/shoulder restraint is not effective in a far-side crash (impact is opposite to the occupant location) since the occupant may slip out of the shoulder harness. The present comprehensive study was designed to delineate the biomechanics of far-side planar crashes. The first part of the study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Placing the horizontal belt below the iliac crest, or placing the diagonal belt above the clavicle is a maneuver many passengers do not realize is dangerous, thus leading to undesired collateral injuries. Lastly, with respect to the design of seat belts, there are studies demonstrating that the current system of three-point retention does not protect the user from certain displacements within the vehicle that may occur with different types of collision (19). Moreover, it has been shown that elderly patients wearing seat belts suffer from severe injuries from a crash even when traveling at low velocity, and the thoracic region of the body is most frequently affected (20).…”
Section: Discussionmentioning
confidence: 97%
“…Placing the horizontal belt below the iliac crest, or placing the diagonal belt above the clavicle is a maneuver many passengers do not realize is dangerous, thus leading to undesired collateral injuries. Lastly, with respect to the design of seat belts, there are studies demonstrating that the current system of three-point retention does not protect the user from certain displacements within the vehicle that may occur with different types of collision (19). Moreover, it has been shown that elderly patients wearing seat belts suffer from severe injuries from a crash even when traveling at low velocity, and the thoracic region of the body is most frequently affected (20).…”
Section: Discussionmentioning
confidence: 97%
“…Possible mechanisms of injury may be ‘jack-knifing’ forwards over a seatbelt or ‘submarining’ effects resulting in abdominal injuries as the maladjusted lap belt rides up over the iliac spines and injures solid organs and major vessels directly. [ 17 18 ] Lap belt injuries are associated with pediatric spinal cord injury in improperly restrained children. Several specific characteristics make children especially vulnerable: They have a higher center of gravity than adults, generating greater distraction forces and lap belts tend to lie over the abdomen instead of the pelvis because the iliac crests are not yet fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results of torso slippage were found in a computational analysis of human response in a far-side impact [26] . The ineffectiveness of shoulder harness has also been confirmed by Kumaresan et al [5] and Digges et al [27] , among others. It was noted that the intrusion of the door of a sedan (2004 Ford Taurus) can be as high as 700mm for striking vehicles such as a GMC-1500 pickup truck, at a delta-V of 28kmph…”
Section: Head Injuries In Far-side Crashesmentioning
confidence: 62%
“…When unrestrained, the risk was higher for frontal collisions (OR=8.0, p=0.0046) and even greater for far-side impacts (OR=23.0, p=0.0018). Despite their evident protection in frontal crashes, seat belts have been known to be ineffective in far-side crashes [5,21] . Table 2.1 shows some factors that significantly affect the risk of a severe driver injury.…”
Section: Effects Of Safety Restraint Usage On Injuriesmentioning
confidence: 99%
See 1 more Smart Citation